2017
DOI: 10.1177/2040206617740303
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of an antiviral assay system and identification of severe fever with thrombocytopenia syndrome virus inhibitors

Abstract: AimsSevere fever with thrombocytopenia syndrome (SFTS) is an emerging tick-borne infectious disease. SFTS is epidemic in Asia, and its fatality rate is around 30% in Japan. The causative virus severe fever with thrombocytopenia syndrome virus (SFTSV) is a phlebovirus of the family Phenuiviridae (the order Bunyavirales). Although effective treatments are required, there are no antiviral agents currently approved for clinical use. Ribavirin and favipiravir were examined for their anti-SFTSV activity and found to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 24 publications
(31 reference statements)
0
23
0
Order By: Relevance
“…Because there are limited reports regarding antiviral effects of CA or chlorogenic acid in vivo (Wang et al, 2009;Ding et al, 2017), further studies are needed. Baba et al (2017) showed that amodiaquine and other halogen molecules effectively inhibited the propagation of SFTSV in vitro. Amodiaquine is widely used as an antimalarial drug and can be administered at a low cost.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because there are limited reports regarding antiviral effects of CA or chlorogenic acid in vivo (Wang et al, 2009;Ding et al, 2017), further studies are needed. Baba et al (2017) showed that amodiaquine and other halogen molecules effectively inhibited the propagation of SFTSV in vitro. Amodiaquine is widely used as an antimalarial drug and can be administered at a low cost.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few reports have indicated resistance to favipiravir in vitro (Delang et al, 2014;Goldhill et al, 2018). As shown in Tables 1, 2 favipiravir significantly inhibits SFTSV replication in vitro (Tani et al, 2016;Baba et al, 2017) and in vivo (Tani et al, 2016(Tani et al, , 2018Smee et al, 2018). Furthermore, the IC 90 of favipiravir (22 µM) in Vero cells (Tani et al, 2016) was lower than that of ribavirin (263 µM) (Shimojima et al, 2014).…”
Section: Favipiravirmentioning
confidence: 98%
See 1 more Smart Citation
“…It is known that AQ inhibits EBOV replication in vivo [58]. A recent study demonstrated that AQ was active against severe fever with thrombocytopenia syndrome (SFTS) caused by SFTS virus (SFTSV) [163].…”
Section: Amodiaquine and Emerging Virusesmentioning
confidence: 99%
“…Coronaviridae CoV Chloroquine in vitro [145][146][147] Picornaviridae Enteroviruses Chloroquine in vitro [160] Chloroquine in vitro/in vivo (mouse) [161] Filoviridae EBOV Chloroquine in vitro [142,143] in vivo [142] Artesunate, amodiaquine in vivo [58] Mefloquine in vitro [132] Retroviridae HIV Artemisinin in vitro [23] Doxycycline in vitro [23] Mefloquine, toremifene, posaconazole in vitro [132] Chloroquine in vitro [151,157,158] in vivo [155] Chloroquine, hydroxychloroquine in vitro [152][153][154]156] Phenuiviridae SFTSV Amodiaquine In vitro [163] Among the aryl-aminoalcohols, the use of MQ in the treatment of JCPyV infection has been extensive, although with contradictory outcomes. Among the aminoquinolines, both CQ and hydroxyCQ showed promising results in reducing the replication of some emerging viruses, such as DENV and ZIKV.…”
Section: Virus Family Virus Species Drug Type Of Study (Model) Referementioning
confidence: 99%